Narrative Medicine: A Writing Workshop Curriculum for Residents - Abigail Ford Winkel (Association of American Medical Colleges, 2016)
Abstract Introduction Reflection is a critical part of the learning cycle. Narrative medicine has been shown to help physicians-in-training develop both empathy and professional identity. A narrative medicine curriculum focused on the experience of the physician and challenging patient experiences creates opportunities in which to process complicated aspects of the experience of both patient and physician with other members of the training community. Methods Fifteen 1-hour small-group reflective writing workshops comprise a 2-year narrative medicine curriculum. Each workshop uses selected literature to focus a discussion and a prompt for written reflection and can be integrated into a didactic curriculum. Teacher guides have been created to help untrained preceptors lead small-group sessions. Feedback forms are distributed to participating residents. Results Out of 29 total residents enrolled at one program, 23 residents completed feedback forms, and 16 (69%) reported that the reflective writing sessions were relevant to their work as obstetrician-gynecologists. Residents stated the best parts of the course were reading and writing (n = 6; 27%), sharing writings with colleagues (n = 5; 21%), and having positive experiences with members of their community (n = 6; 27%). Some residents reported difficulty sharing their private reflections (n = 4; 17%). Discussion A narrative medicine curriculum is a powerful tool for promoting reflection about the challenging work of training in obstetrics and gynecology and other specialties. Reflective writing workshops have been found to be acceptable to obstetrics and gynecology residents, and the curriculum has been successfully implemented at several training programs.